The Real-World Cost-Effectiveness of Coronary Artery Bypass Surgery Versus Stenting in High-Risk Patients: Propensity Score-Matched Analysis of a Single-Centre Experience - Ariyaratne, T.; Ademi, Z.; Huq, M.; Rosenfeldt, F.; Duffy, S.; Parkinson, B.; Yap, C.; Smith, J.; Billah, B.; Yan, B.; Brennan, A.; Tran, L.; et al. (Adis Information Ltd, 2018)
Background: There are limited economic evaluations comparing coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) for multi-vessel coronary artery disease (MVCAD) in contemporary, routine clinical practice. Objective: The aim was to perform a cost-effectiveness analysis comparing CABG and PCI in patients with MVCAD, from the perspective of the Australian public hospital payer, using observational data sources. Methods: Clinical data from the Melbourne Interventional Group (MIG) and the Australian and New Zealand Society of Cardiac and Thoracic Surgeons (ANZSCTS) registries were analysed for 1022 CABG (treatment) and 978 PCI (comparator) procedures performed between June 2009 and December 2013. Clinical records were linked to same-hospital admissions and national death index (NDI) data. The incremental cost-effectiveness ratios (ICERs) per major adverse cardiac and cerebrovascular event (MACCE) avoided were evaluated. The propensity score bin bootstrap (PSBB) approach was used to validate base-case results. Results: At mean follow-up of 2.7 years, CABG compared with PCI was associated with increased costs and greater all-cause mortality, but a significantly lower rate of MACCE. An ICER of $55,255 (Australian dollars)/MACCE avoided was observed for the overall cohort. The ICER varied across comparisons against bare metal stents (ICER $25,815/MACCE avoided), all drug-eluting stents (DES) ($56,861), second-generation DES ($42,925), and third-generation of DES ($88,535). Moderate-to-low ICERs were apparent for high-risk subgroups, including those with chronic kidney disease ($62,299), diabetes ($42,819), history of myocardial infarction ($30,431), left main coronary artery disease ($38,864), and heart failure ($36,966). Conclusions: At early follow-up, high-risk subgroups had lower ICERs than the overall cohort when CABG was compared with PCI. A personalised, multidisciplinary approach to treatment of patients may enhance cost containment, as well as improving clinical outcomes following revascularisation strategies.